Soluble Phenolic Composition Tailored by Germination Conditions Accompany Antioxidant and Anti-Inflammatory Properties of Wheat - Irene Tomé-Sánchez; Ana Belén Martín-Diana; Elena Peñas; Sara Bautista-Expósito; Juana Frias; Daniel Rico; Lorena González-Maillo; Cristina Martinez-Villaluenga (Antioxidants, 2020)
Knowledge on the specific variation in the phenolic composition of wheat defined by germination conditions and its relationship with antioxidant and anti-inflammatory properties of sprouts would be useful to improve the functional value of wheat-derived products. Variation in soluble phenolic composition, antioxidant and anti-inflammatory potential of wheat was examined in a range of germination temperature (12–21 °C) and time (1–7 d). Response surface methodology was applied for building lineal and quadratic models to find optimal germination conditions to improve nutraceutical value of wheat sprouts using the desirability (D) function. Phenolics were determined by HPLC-DAD-ESI-MS. In vitro biochemical methods and lipopolysaccharide stimulated RAW264.7 macrophages were used to determine antiradical and anti-inflammatory activities of wheat sprouts. Accumulation of soluble phenolic acids, flavone C-glycosides and lignans in sprouts was positively influenced by germination temperature and time. Increased concentration of individual polyphenols was directly associated with improved ability of sprouts for radical scavenging and reduction of tumor necrosis factor α and interleukin 6 in macrophages. Optimal desirability (D = 0.89) for improved nutraceutical value of wheat sprouts was achieved at 21 °C for 7 d. This information would be useful for food industry aiming at producing wheat-based products with better nutritional and healthy properties.